Synthesis and Biological Evaluation of Substituted 3‐Isoxazolethioethers as Antileishmanial and Antibacterial Agents. Issue 25 (1st July 2022) - Bisht, Shweta; Kumar, Lalan; Kaul, Grace; Akhir, Abdul; Saxena, Deepanshi; Chopra, Sidharth; Karthik, R.; Goyal, Neena; Batra, Sanjay
Abstract: The synthesis of substituted 3‐isoxazolethioethers and their bioevaluation as anti‐leishmanial and anti‐bacterial agents are described. The DBU‐catalyzed thioetherification of substituted 3‐nitroisoxazoles via nucleophilic aromatic substitution (SN Ar) reaction using aromatic, aliphatic and heteroaromatic thiols gave the title compounds in good yields. These 3‐thioisoxazole derivatives were synthetically modified to prepare new compounds including 3‐phenylbenzo[b]isoxazolo[4, 3‐ f ][1, 4]thiazepin‐4(5 H )‐ones. Four compounds displayed promising activity against amastigote stage of L. donovani whereas two compounds displayed good antibacterial effect. Abstract : The synthesis of 3‐isoxazolethioethers via SN Ar reaction between 3‐nitroisoxazoles and thiols, their derivatization and evaluation as anti‐leishmanial and anti‐bacterial agents have been described.